2013
DOI: 10.1063/1.4773368
|View full text |Cite
|
Sign up to set email alerts
|

Electrical characterization of inorganic-organic hybrid photovoltaic devices based on silicon-poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate)

Abstract: Hybrid organic-inorganic photovoltaic devices based on nanostructured silicon and poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) hybrid devices present excellent light harvesting capabilities as well as a simple fabrication process. Unlike the metal/Si junction, PEDOT:PSS solution can be solution-casted onto the silicon surface structure to build up hybrid photovoltaic devices without using vacuum deposition techniques. Detailed electronic characterization at PEDOT:PSS/Si heterojunctions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 25 publications
(32 reference statements)
0
26
1
Order By: Relevance
“…The calculated IQE spectra [ Figure 4(b)] showed enhancement from surface nanostructures but exclude any anti-reflective effect associated with the surface nanostructures. The discrepancy between this work and the previously reported literature 19 in the short wavelength range (300 nm-400 nm) of the IQE is probably due to the difference in the reflectance. The results from the IQE spectra indicated that the improvement in the EQE and J sc is attributed to the antireflective effect and higher carrier collection efficiency.…”
contrasting
confidence: 99%
“…The calculated IQE spectra [ Figure 4(b)] showed enhancement from surface nanostructures but exclude any anti-reflective effect associated with the surface nanostructures. The discrepancy between this work and the previously reported literature 19 in the short wavelength range (300 nm-400 nm) of the IQE is probably due to the difference in the reflectance. The results from the IQE spectra indicated that the improvement in the EQE and J sc is attributed to the antireflective effect and higher carrier collection efficiency.…”
contrasting
confidence: 99%
“…Most of studies on the film deposition of PEDOT:PSS has been performed using spin coating (SC) followed by thermal annealing to remove residual solvent. Promising efficiencies of 9–13% have already been reported with no use of p–n junction and transparent conductive oxide such as indium tin oxide (ITO) . For further higher efficiency, an enhanced internal light trapping approach such as textured c‐Si by wet etching, nanometer‐sized pillar, antireflection (AR) layer coating, and photonic crystal has been extensively studied .…”
Section: Introductionmentioning
confidence: 99%
“…[259][260][261][262][263][264][265][266][267][268][269] Compared with the conventional fabrication process of crystalline Si solar cells these hybrid solar cells could be fabricated at significantly lower costs. Instead of the high-temperature diffusion or expensive implantation process to form a p-n junction, simply a polymer layer was added on top of a n-type Si wafer.…”
Section: Recent Concepts and Pathways To Higher Efficienciesmentioning
confidence: 99%